Perancangan dan Implementasi Sistem Informasi Pelayanan Jam'iyah Umroh Hafas - Irma Yunita; Muhammad Ali Ridla (Department of Science and Technology Ibrahimy University, 2019)
The servicing done by jam'iyah umroh hafas (a group which provide umrah service) still use conventional procedure, namely by using form paper during the registration which obliges pilgrims to meet with the organizer. Also in the next process all is done with a face to face model, so that for the management of pilgrims each package the officer must carefully sort it out. This greatly affects the service process, in which officers must be really careful to group installments from pilgrims, as well as prepare data for processing to passports and travel. Therefore, in an effort to provide optimal, fast and appropriate services for hafas pilgrims, it is necessary to adopt the Customer Relationship Management contained in e-business, as well as to engineer software that can facilitate officers in completing all pilgrims administrative who will go to makkah. Designing this system uses the V-Model method in which each stage is validated and verified so that the system that is produced really meets the needs of the users and helps the officers to better administer the needs of the pilgrims.